Lineamientos de integración territorial en la conurbación Santiago de Cali – Jamundí (2020)
The demographic and territorial growth of Cali progressively puts more pressure on the carrying capacity of road infrastructure, urban equipment and coverage of public services of urban perimeters, generating different degrees of commutation, which in turn generate conurbations with the municipalities of Yumbo, Palmira and Jamundí. Cities like Barranquilla, Pereira or Medellín, with similar situations, ended up calling their territory a metropolitan area. This brings together several municipalities and allows them to potentiate their own resources in search of territorial integration projects. Although the Cali metropolitan area is not legally recognized, it actually works. And he presents his best projection opportunity in the Cali - Jamundí conurbation. Because due to its increasing commutation, this conurbation located outside the expansion area of Cali, delimits the urban perimeters of both municipalities, which allows exploring in advance the necessary guidelines for the integration of the territory.